Mast Cells and Dendritic Cells as Cellular Immune Checkpoints in Immunotherapy of Solid Tumors - Kalkusova, Katerina; Smite, Sindija; Darras, Elea; Taborska, Pavla; Stakheev, Dmitry; Vannucci, Luca; Bartunkova, Jirina; Smrz, Daniel (International journal of molecular sciences, 2022)
The immune checkpoint inhibitors have revolutionized cancer immunotherapy. These inhibitors are game changers in many cancers and for many patients, sometimes show unprecedented therapeutic efficacy. However, their therapeutic efficacy is largely limited in many solid tumors where the tumor-controlled immune microenvironment prevents the immune system from efficiently reaching, recognizing, and eliminating cancer cells. The tumor immune microenvironment is largely orchestrated by immune cells through which tumors gain resistance against the immune system. Among these cells are mast cells and dendritic cells. Both cell types possess enormous capabilities to shape the immune microenvironment. These capabilities stage these cells as cellular checkpoints in the immune microenvironment. Regaining control over these cells in the tumor microenvironment can open new avenues for breaking the resistance of solid tumors to immunotherapy. In this review, we will discuss mast cells and dendritic cells in the context of solid tumors and how these immune cells can, alone or in cooperation, modulate the solid tumor resistance to the immune system. We will also discuss how this modulation could be used in novel immunotherapeutic modalities to weaken the solid tumor resistance to the immune system. This weakening could then help other immunotherapeutic modalities engage against these tumors more efficiently.
Keywords: nádorové mikroprostředí; Immune Checkpoint Inhibitors; dendritické buňky; inhibitory kontrolních bodů; nádory; lidé; Neoplasms; Tumor Microenvironment; mastocyty; Humans; Mast Cells; imunoterapie; Dendritic Cells; Immunotherapy